2021
DOI: 10.3390/polym13081300
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Chitosan-Derived Biomaterials Modified with Kalanchoe pinnata as Potential Hemostatic Agents—Development and Characterization

Abstract: Massive blood loss is still a great challenge for modern medicine. To stop the hemorrhage during the surgery or after injury apart from suturing or electrocoagulation, the most efficient method of hemostasis restoration is the use of hemostatic agents. Although there are numerous products on the market, there is still a need for biomaterials that are capable of fast and efficient bleeding management without affecting wound closure or embolism. Chitosan is known for its hemostatic activity; however, its quite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Given the importance of using non-toxic dressings to ensure the survival, proliferation, and proper functioning of cells in the wound microenvironment, several efforts have been devoted to investigating the in vitro cytotoxicity of CS, GSE, and PE. ,,, For instance, Biranje et al demonstrated the nontoxic effects of CS/carrageenan composites against human dermal fibroblasts, attributing these effects to the porous and hydrophilic nature as well as the positive charge of the composites. Similarly, other CS-based materials have shown non-toxic and even proliferative effects in cell lines such as mouse osteoblast cell lines, human umbilical vein endothelial cells, and L-929 fibroblasts. , In addition, the nontoxic effects of PE and GSE have been previously demonstrated in HaCaT cells and fibroblasts. , The biocompatibility properties of these extracts have been mainly attributed to the presence of PAs in their structures, which has shown favorable effects on cell proliferation. , Our findings corroborate that the presence of GSE and PE has a beneficial effect on HaCaT cells.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Given the importance of using non-toxic dressings to ensure the survival, proliferation, and proper functioning of cells in the wound microenvironment, several efforts have been devoted to investigating the in vitro cytotoxicity of CS, GSE, and PE. ,,, For instance, Biranje et al demonstrated the nontoxic effects of CS/carrageenan composites against human dermal fibroblasts, attributing these effects to the porous and hydrophilic nature as well as the positive charge of the composites. Similarly, other CS-based materials have shown non-toxic and even proliferative effects in cell lines such as mouse osteoblast cell lines, human umbilical vein endothelial cells, and L-929 fibroblasts. , In addition, the nontoxic effects of PE and GSE have been previously demonstrated in HaCaT cells and fibroblasts. , The biocompatibility properties of these extracts have been mainly attributed to the presence of PAs in their structures, which has shown favorable effects on cell proliferation. , Our findings corroborate that the presence of GSE and PE has a beneficial effect on HaCaT cells.…”
Section: Resultssupporting
confidence: 85%
“…Similarly, other CS-based materials have shown non-toxic and even proliferative effects in cell lines such as mouse osteoblast cell lines, 46 human umbilical vein endothelial cells, 19 and L-929 fibroblasts. 18,40 In addition, the nontoxic effects of PE and GSE have been previously demonstrated in HaCaT cells and fibroblasts. 8,9 The biocompatibility properties of these extracts have been mainly attributed to the presence of PAs in their structures, which has shown favorable effects on cell proliferation.…”
Section: 4mentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, the plant known as Chiriyuyo in Ecuador is a plant species belonging to the family Crassulaceae (species Kalanchoe pinnata , native to Africa and Madagascar). It has been found that the extracts obtained from Chiriyuyo (CE) leaves and stems have good antimicrobial activity against bacteria, fungi and viruses [ 19 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%